A note on the slip effects of an Oldroyd 6-constant fluid: Optimal homotopy asymptotic method - Manzoor, Tareq; Iqbal, S.; Shah, Mohd Asif (Frontiers in Physics, 2022)
We study here the effectiveness of the Optimal Homotopy Asymptotic Method (OHAM) in solving nonlinear differential equations of Non-Newtonian fluid. To this consequence, we consider the Oldroyed 6-contant fluid, when it demonstrates slippage between the plate and fluid generates nonlinear boundary value problems. The problems of plane Couette flow, generalized Couette flow and plane poiseuille flow are considered. Graphs of the results are plotted to show the performance of the method in terms of velocity profile. It is observed that method is quite easy to implement, having latent potential to handle such kind of nonlinear problems and yield accurate results at minimum to low computational work.